2004
DOI: 10.2754/avb200473020291
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity for Humans of Cow Milk Caseins, Casein Hydrolysate and Casein Hydrolysate Fractions

Abstract: Nentwich I., Szépfalusi Zs., Kunz C., Spuergin P., Urbanek R.: Antigenicity for Humans of Cow Milk Caseins, Casein Hydrolysate and Casein Hydrolysate Fractions. Acta Vet. Brno 2004, 73: 291-298. Cow milk casein consists of several fractions each of which have different structure and differing antigenicity. The aim of the study was to investigate the capacity of cow milk casein, casein fractions, casein hydrolysate and its fractions to bind human IgG antibodies (antigenicity).Whole cow milk, bovine casein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…It has been shown that exposure to cow milk protein during the first 3 months of life results in high levels of IgG subclass antibodies, detected even at 8 years of age (Jenmalm and Björkstén 1998 ). Similar findings were reported by Nentwich et al 2004 who demonstrated the presence of specific IgG antibodies against cow’s milk protein not only in the serum of children and an adult with CMA, but also in the serum of healthy people consuming cow’s milk. It was demonstrated that CMA patients are characterized by elevated levels of specific IgE levels as well as the specific IgG levels (Shek et al 2005 ; Meulenbroek et al 2013 ).…”
Section: Resultssupporting
confidence: 90%
“…It has been shown that exposure to cow milk protein during the first 3 months of life results in high levels of IgG subclass antibodies, detected even at 8 years of age (Jenmalm and Björkstén 1998 ). Similar findings were reported by Nentwich et al 2004 who demonstrated the presence of specific IgG antibodies against cow’s milk protein not only in the serum of children and an adult with CMA, but also in the serum of healthy people consuming cow’s milk. It was demonstrated that CMA patients are characterized by elevated levels of specific IgE levels as well as the specific IgG levels (Shek et al 2005 ; Meulenbroek et al 2013 ).…”
Section: Resultssupporting
confidence: 90%
“…Whey proteins (α‐lactalbumin [ALA], β‐lactoglobulin [BLG], bovine serum albumin) and caseins are considered as the main cow's milk antigens (Räsänen et al. 1992; Nentwich et al. 2004), and they cause an immunologically mediated adverse reaction (Savilahti et al.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the cow's milk allergy ranges from 1.9 to 7.5% of the population (Järvinen and Suomalainen 2001). For this reason, the application of lactic acid bacteria (LAB) in hydrolysis of milk proteins may have important effects on milk digestibility, on the production of bioactive peptides and may decrease milk allergenicity and lactose intolerance (Nentwich et al. 2004; Prioult et al.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach to decrease antigenic/allergenic potential of milk proteins is bacterial fermentation. During the fermentation by LAB, the proteolysis of milk proteins is followed by a reduction of the number of epitopes and consequently by a decrease in antigenicity of hydrolyzed proteins (Cross et al 2001;Bertrand-Harb et al 2003;Nentwich et al 2004). It was already reported that some LAB reduce the antigenic response of milk proteins (Wroblewska et al 1995;Kleber et al 2006;Bu et al 2010).…”
Section: Introductionmentioning
confidence: 99%